Elementary Teachers' Acceptance of Merdeka-Based Digital Teaching and Learning Media: A Study of the UTAUT Model - Meilandari, Aesti; Abidin, Yunus; Kurniawan, Dede Trie; Ramadhan, Taufik (FKIP Universitas Lampung, 2025)
Elementary Teachers' Acceptance of Merdeka-Based Digital Teaching and Learning Media: A Study of the UTAUT Model. Objective: The purpose of this study is to assess the level of acceptability among elementary school teachers towards Merdeka-based learning media and teaching materials. It is imperative to comprehend the factors that influence teacher acceptability in order to guarantee the efficacy of digital learning media, given the growing demand for technology integration in education. Methods: The correlational survey method along with the Unified Theory of Acceptance and Use of Technology (UTAUT) model approach are employed in this investigation. As many as 100 elementary school instructors in Lampung Province who have experience using Merdeka-based media and teaching materials were included as respondents. Data analysis was conducted using the Structural Equation Modeling (SEM) technique to test the relationships between variables in the acceptance model, and data collection was implemented through closed questionnaires. Findings: Teachers' acceptability levels are positively affected by media and instructional materials that adhere to the Merdeka framework. The primary factors that contribute to this acceptance are attitudes toward technology, affective needs, routines of using ICT, perceptions of learning opportunities, self-efficacy, and social influence. Teachers' behavioral intentions and ICT usage patterns can be significantly elucidated by the SEM model that was developed. Self-efficacy and effort expectancy variables were found to have direct effects, while social influence tended to have a lower impact. Conclusion: Teachers’ acceptance of educational innovations can be improved through the use of interactive and challenging technology-based learning media. This acceptance has favorable consequences for the adoption of innovative teaching strategies that are consistent with the requirements of 21st-century education, as well as for the enhancement of student engagement, learning perseverance, and a profound comprehension of the subject matter. Keywords: merdeka-based teaching and learning media, teacher acceptance model, UTAUT Model, elementary teacher.